2008
DOI: 10.1164/rccm.200711-1657oc
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus in Lung Transplant Recipients and Comparison to Respiratory Syncytial Virus

Abstract: Human metapneumovirus is a leading cause of acute respiratory tract illness in lung transplant recipients. The incidence and clinical spectrum at presentation are similar to RSV, although the latter seems to be associated with a higher risk of chronic rejection. We recommend testing of nasopharyngeal aspirates for human metapneumovirus with polymerase chain reaction to assess local epidemiologic patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(138 citation statements)
references
References 33 publications
5
129
0
4
Order By: Relevance
“…Given this, HMPV is responsible for many hospitalized cases (28,30,43,241), and infections in the elderly can result in death (28,30,43). Pneumonia has been documented for 40% of HMPV-infected frail elderly subjects (28,117,149). It has been reported that the most frequent admission diagnoses for HMPV infection in the elderly are acute bronchitis, COPD exacerbation, pneumonia, and congestive heart failure (241).…”
Section: Risk Groups Other Than Childrenmentioning
confidence: 99%
“…Given this, HMPV is responsible for many hospitalized cases (28,30,43,241), and infections in the elderly can result in death (28,30,43). Pneumonia has been documented for 40% of HMPV-infected frail elderly subjects (28,117,149). It has been reported that the most frequent admission diagnoses for HMPV infection in the elderly are acute bronchitis, COPD exacerbation, pneumonia, and congestive heart failure (241).…”
Section: Risk Groups Other Than Childrenmentioning
confidence: 99%
“…Infections can be acquired nosocomially or in the community. In lung transplant patients, RSV is associated with a higher risk of chronic rejection and bronchiolitis obliterans syndrome compared to hMPV [103]. In HIV-infected South African children, the incidence of hMPV and RSV hospitalisation has been shown to be 2.5 and 5.4 times higher, respectively, compared to HIVnegative children [104,105].…”
Section: Specific Populationsmentioning
confidence: 99%
“…Importantly, during the 2009 influenza A H1N1 pandemic, a significant number of cases of acute allograft injury due to influenza were observed (126)(127)(128). Severe cases of other CARVs, such as respiratory syncytial virus (RSV), parainfluenza virus and human metapneumovirus, have been described (129)(130)(131).…”
Section: Infection By Community-acquired Respiratory Virusesmentioning
confidence: 99%